2014
DOI: 10.1155/2014/739494
|View full text |Cite
|
Sign up to set email alerts
|

Store-Operated Ca2+Entry Does Not Control Proliferation in Primary Cultures of Human Metastatic Renal Cellular Carcinoma

Abstract: Store-operated Ca2+ entry (SOCE) is activated following depletion of the inositol-1,4,5-trisphosphate (InsP3)-sensitive Ca2+ pool to regulate proliferation in immortalized cell lines established from either primary or metastatic lesions. The molecular nature of SOCE may involve both Stim1, which senses Ca2+ levels within the endoplasmic reticulum (ER) Ca2+ reservoir, and a number of a Ca2+-permeable channels on the plasma membrane, including Orai1, Orai3, and members of the canonical transient receptor (TRPC1–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 63 publications
2
38
0
Order By: Relevance
“…Knock-down of STIM1 expression resulting in almost complete inhibition of SOCE activity did not affect proliferation, as shown for HEK293 [21], endothelial cells [22] and differentiating myoblasts [94]. In metastatic renal carcinoma cells (mRCC), the pharmacological blockade of SOCE did not interfere with mRCC proliferation despite proper SOCE functioning in these cells [95]. In view that, store-independent Ca 2+ signaling triggers cell proliferation of some cell lines.…”
Section: Deletion Of Stim Protein Expression In T Reg Cells Influencementioning
confidence: 81%
“…Knock-down of STIM1 expression resulting in almost complete inhibition of SOCE activity did not affect proliferation, as shown for HEK293 [21], endothelial cells [22] and differentiating myoblasts [94]. In metastatic renal carcinoma cells (mRCC), the pharmacological blockade of SOCE did not interfere with mRCC proliferation despite proper SOCE functioning in these cells [95]. In view that, store-independent Ca 2+ signaling triggers cell proliferation of some cell lines.…”
Section: Deletion Of Stim Protein Expression In T Reg Cells Influencementioning
confidence: 81%
“…Moreover, Kim et al (50) reported an increase expression level of ORAI1, but not STIM1 or ORAI3, in RCC: pharmacological inhibition of SOCE or ORAI1 or STIM1 downregulation significantly impaired cell proliferation as well as cell migration of RCC Caki-1 cell lines. However, these data are a bit controversial and were not confirmed by Dragoni and colleagues (22), who could not find any role for SOCE in cell proliferation of freshly isolated RCC metastatic cells from patients.…”
Section: Sustaining Proliferative Signaling/evading Growth Suppressorsmentioning
confidence: 90%
“…In this research, the authors demonstrate the involvement of Orai1 in VEGF activated in vitro tubulogenesis and in vivo angiogenesis using the chick chorioallantoic membrane model (56). Similarly to HUVEC, suppression of ORAI1 in endothelial progenitor cells (EPCs) prevents VEGF-mediated SOCE and tubule formation (22,56). Moreover, EPCs isolated from RCC patients (RCC-EPCs) display an increased SOCE, which correlates with ORAI1, STIM1, and TRPC1 overexpression when compared with EPCs from healthy patients: genetic suppression of STIM1, ORAI1, and TRPC1 affects SOCE in RCC-EPCs (59).…”
Section: Inducing Angiogenesismentioning
confidence: 90%
“…Recently, their origin from late EPCs or differentiated endothelial cells was demonstrated [13]. EPCs are mobilized either from the bone marrow or the arterial area to replace dysfunctional endothelial cells and, using different molecular mechanisms, play a pivotal role in blood perfusion of ischemic and tumoral tissues [1427]. Although haemangiomas are common lesions of the head and neck (over half of all hemangiomas are located in this region), in the nasal cavity and paranasal sinuses they are rare [1,3,5].…”
Section: Discussionmentioning
confidence: 99%